The implementation, comprehensiveness, and skills provision of the Youth Employment Service (YES) among young Black women in Gauteng townships - Velelo, Lukhanyo (Department of Sociology, 2024)
South Africa (SA) is currently the most unequal nation in the world among countries with reliable statistics, with some of the highest poverty levels and youth unemployment rates. However, there are various youth employment interventions (YEIs) that have been introduced to address youth unemployment. One of the most recent YEIs is the Youth Employment Service (YES), which is supported by business, the state, and organised labour. YES is a workexperience programme that aims to provide a steppingstone towards sustainable employment. Research has shown that comprehensive YEIs are more effective and impactful, and skillsproviding programmes have been successful in the labour market. Therefore, this paper aims to assess YES and answer the question of how comprehensive it is and what skills it provides for the labour market. This assessment is specifically focused on YES's work-placement programme and not its business development programme. This paper utilises mixed methods, including purposive sampling of 20 young Black women from low-income communities in Gauteng. While the sample size is small and the findings are not representative, they still provide valuable insightsinto YES. The primary data was collected through individual mini surveys online (quantitative research) and semi-structured focus group discussions (qualitative research) in person. The data was analysed statistically using descriptive statistics and bivariate regression, and thematically using MS Excel and NVivo. The paper's findings indicate that the participants require skills and psychosocial support, among other things. It argues for YEIs that meet participants' needs. The study found that YES effectively provides soft skills directly and hard skills indirectly through host companies. The findings show that YES is comprehensive in its approach to supporting and empowering participants, which meets their needs, making YES a youth developmental programme. The paper also argues that YES differs from previous Government-Backed Programmes (GBPs) of YEIs. While YES is an employability, job accessibility and job creation programme like previous GBPs, it is also a job-supporting, job coordination and financial literacy programme, unlike many of the previous GBPs. The study found that YES does commendable work, such as providing work experience, while trying to contribute to addressing unemployment, a complex issue. However, YES is still in its trial stages and there are some challenges, such as a limited provision of career development. This means that while YES is comprehensive and provides skills, it also needs to be strengthened. The paper recommends that YES develop concrete plans to standardise the programme and provide it to all its applicants, among other ways to strengthen the programme.